Would you feel happier if you have more protection behaviour? A panel survey of university students in Japan. Issue 4 (3rd April 2019) - Ye, Shaoyu; Ho, Kevin K.W.
ABSTRACT: It is suggested that the young generations' low levels of privacy concerns might lead to undesirable behaviours that have negative effects on their subjective well-being. This study aims to investigate what kind of causal relationship would exist among the young generations' privacy concerns, protection behaviours and subjective well-being in Japan, considering the effects of demographic factors (age, gender) and Internet access time via computers and smartphones. A two-wave panel survey targeting university students was conducted and 163 responses became the analysed data. The following results were observed: (a) Students' privacy concerns had positive direct effects on their protection behaviours, along with their time spent accessing the Internet through computers; and (b) Their protection behaviours, as well as their time spent accessing the Internet through computers, had negative direct effects on their subjective well-being.